2018
DOI: 10.1155/2018/9756468
|View full text |Cite
|
Sign up to set email alerts
|

Apathy following Bilateral Deep Brain Stimulation of Subthalamic Nucleus in Parkinson’s Disease: A Meta-Analysis

Abstract: Bilateral deep brain stimulation of subthalamic nucleus (STN-DBS) has proven effective in improving motor symptoms in Parkinson's disease (PD) patients. However, psychiatric changes after surgery are controversial. In this study, we specifically analyzed apathy following bilateral STN-DBS in PD patients using a meta-analysis. Relevant articles utilized for this study were obtained through literature search on PubMed, ScienceDirect, and Embase databases. The articles included were those contained both pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Indeed, satisfaction with DBS is high in patients with greater than 5 years of therapy [24] though there are no data currently available regarding satisfaction based on the genetic status. Furthermore, we did not assess for apathy in this vulnerable population [25], which may also have an impact on desire for genetic data. Lastly, the study is limited by our assessment of only DBS subjects and future studies should be designed to compare subjects with and without DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, satisfaction with DBS is high in patients with greater than 5 years of therapy [24] though there are no data currently available regarding satisfaction based on the genetic status. Furthermore, we did not assess for apathy in this vulnerable population [25], which may also have an impact on desire for genetic data. Lastly, the study is limited by our assessment of only DBS subjects and future studies should be designed to compare subjects with and without DBS.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that STN DBS reduces anxiety, pain, and nonmotor fluctuations [ 27 ] and improves sleep and generally patients' quality of life [ 23 , 28 ]. Nevertheless, adverse effects on some neuropsychiatric, cognitive, and behavioural symptoms following STN DBS have been reported such as increased apathy [ 27 , 29 ], impulsivity [ 27 ], hypomania [ 30 , 31 ], and even attempted or completed suicide [ 22 , 32 ]. STN DBS may also result in worsening of memory and overall cognition [ 33 , 34 ], processing speed [ 33 ], attention [ 33 ], verbal fluency [ 33 35 ], and executive functions [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…They hypothesized a direct influence of STN-DBS on the limbic system by diffusion of stimulus to the medial limbic compartment of STN. Recently, a metanalysis assessing apathy following bilateral DBS of the STN in PD concluded that the reduction of dopaminergic medication after surgery may be the cause of worsening apathy in this patient population (167). Other authors have failed to find significant differences in apathy prevalence or severity between surgical and non-surgical patients (168).…”
Section: Adverse Effectsmentioning
confidence: 99%